COMPARATIVE ANALYSIS AND INVESTMENT STRATEGY OF ISLAMIC STOCKS IN THE PRIMARY AND SECONDARY MARKETS - Rozalina Mirwan; Panji Adam Agus Putra; Nandang Ihwanudin (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2026)
The dominance of sharia stocks in the Indonesian capital market, which will reach 62.55% by 2025, is accompanied by an increase in the number of investors, but faced with the challenge of fraudulent practices and violations of sharia principles, so this study aims to analyze the differences in the characteristics of sharia stock investment between the primary market and the secondary market and formulate optimal strategies to ensure sharia compliance. With the qualitative literature study method, the results of the study revealed the fundamental difference that the primary market uses a Syirkah Musahamah (partnership) contract that offers the potential to benefit from lower dividends and initial price and contributes directly to the halal business, but is high risk and limited liquidity. Meanwhile, the secondary market is based on the Ba'i Al Musawamah contract which is a pillar of liquidity and flexibility to diversify and achieve dividends and capital gains, despite facing price fluctuations and commission costs. In conclusion, market choice depends on the investor's profile of the investor's financial objectives, investment period, and risk tolerance of each investor, with sustainable sharia compliance can only be ensured through a comprehensive strategy that synergizes moral integrity (Islamic business ethics), screening technology (SOTS and the Sharia Securities List/DES), analytical competence (fundamental and technical), and increased Islamic financial literacy, with absolute verification requirements issuers through DES in accordance with OJK regulations and DSN-MUI fatwa.